Voltage, Current, and Work Process Monitoring System on CNC Diode Lasers - Zulhijjah, Intan Dwi; Fitriani, Endah; Paramytha IS, Nina; Dasmen, Rahmat Novrianda (LPPM Universitas Dian Nuswantoro, 2025)
The advancement of CNC laser diode technology has transformed manufacturing by enabling high precision cutting and engraving of various materials, yet ensuring reliable operation requires accurate monitoring of electrical and mechanical parameters. This research focused on designing and implementing a real-time monitoring system that integrates the PZEM-004T sensor for electrical measurements and limit switches for safety boundaries in CNC laser diode machines. The system was developed using NodeMCU ESP8266 as the main controller, with results displayed on an LCD 16x2 and alarms generated through a buzzer and relay. Experimental evaluation demonstrated that the system effectively measured voltage, current, power, and energy, with the PZEM-004T showing an average error below 5% compared to reference instruments. The integration of limit switches functioned reliably, preventing mechanical failures and ensuring safe operation within defined limits. Monitoring data supported energy efficiency by identifying power usage patterns and reducing operational risks. Engraving tests confirmed stable performance, with improved detail observed during longer process durations. Overall, the implemented system provides a practical and reliable solution for operational monitoring and mechanical protection, making it particularly suitable for small-scale CNC laser diode applications in industrial, educational, and creative fields.